Sodium 2-(4-amino-(5-(furan-2-yl)-1,2,4-triazole-3-ylthio)acetate, synthesis, study of biochemical indicators of blood serum cows in its use - D. M. Danilchenko; T. V. Zvenigorodska; V. V. Parchenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2017)
Introduction. Heterocyclic system of 1,2,4-triazole is interesting and has a popularity among scientists around the world every year. Most attention today is attracted to the compounds formed by a combination of 1,2,4-triazole and various structural residues of an aliphatic, aromatic, heterocyclic nature. Recent publications on the study of physical, chemical and biological properties of 1,2,4-triazole substituted prove the obvious relevance of the search for potential pharmacologically active molecules is among the water-soluble derivatives of 1,2,4-triazole. It should be noted that 1,2,4-triazole derivatives are successfully used in veterinary practice as original domestic drugs.